THE LECTURERS’ PERCEPTION OF THE IMPLEMENTATION OF ICT FOR CONDUCTING ONLINE LEARNING DURING COVID-19 PANDEMIC - Ade Gorbi Irawan; Kadek Dwi Hendratma Gunawan (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2022)
During the Covid-19 pandemic, integrating information and communication technology (ICT) in the education sector is inevitable. The use of technology was expected to replace face-to-face instruction with online learning. However, not all educators were ready to use ICT for their instruction. Thus, this study aimed to find out the lecturers' perception towards the implementation of online learning and the problems they faced during the Covid-19 pandemic. The subjects of the research were the lecturers at STKIP Agama Hindu Singaraja. There were 40 lecturers involved in this study. They were selected using the saturated sampling technique. The researcher collected the data through a questionnaire. The questionnaire results were analyzed quantitatively using descriptive statistics. Then, the total score of the questionnaire result was classified using a category based on the theoretical ideal reference assessment formula. The finding showed that, in general, the lecturers had a positive perception of the use of ICT for online learning during the Covid-19. Besides, this study also found some problems faced by the lecturers in implementing online learning. Thus, this study concluded that the lecturers believed that using ICT for online learning was the best option they had during the Covid-19 pandemic, even though they should face various challenges in delivering the instruction through online learning.